The stability and in vitro digestion of curcumin emulsions containing Konjac glucomannan. (January 2020) - He, Shenghua; Gu, Cheng; Wang, Deguo; Xu, Weili; Wang, Rongchun; Ma, Ying
Abstract: Konjac glucomannan (KGM) was used to characterize the structure of the curcumin emulsions stabilized with whey protein isolate (WPI). With an increasing concentration of KGM from 0.1% to 0.3%, the fat droplet size decreased significantly (p < 0.05) with increasing KGM content. The retention of curcumin in emulsions with KGM was significantly higher (p < 0.05) than the emulsions without KGM, after heating at 85 °C for 90 min. These two emulsions showed good stability in the pH range of 2–8 in addition to pH 5. Both emulsions with/without KGM were stable at 0–80 mM salt concentration, however the curcumin emulsion with KGM was unstable at 100 mM NaCl concentration. The droplet size analysis and microscopic observations indicated that the aggregation of fat droplets in these two emulsions occurred under simulated gastric fluid (SGF) conditions with a digestion time of 10 min. There were more undigested fat droplets in the curcumin emulsion with KGM than the emulsion without KGM under simulated intestinal fluid conditions after 120 min of digestion. The addition of KGM in WPI-stabilized curcumin emulsions slowed down the release rate of free fatty acids and curcumin from the emulsion droplets. These findings indicated that KGM could be used to achieve a controlled and sustainable release of bioactive compounds from emulsions. Highlights: Konjac glucomannan (KGM) was used to structure the curcumin emulsions. Evaluated the effects of KGM on the stability of curcumin emulsions. Investigated the digestive properties of curcumin emulsions containing KGM.